The Influence of Emotional Intelligence on Disruptive Behaviour Among Adolescents in Public Secondary Schools in Lagos State. (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
This paper examined the influence of emotional intelligence on disruptive behaviour among in-school adolescents in public secondary schools in Lagos State, Nigeria, and explored the effect of gender on these behaviours. Using a cross-sectional design, a total of 1001 adolescents (48.3% male, 51.7% female), aged 1218 years (M = 15.31; SD = 1.49), were sampled across nine public schools in four education districts. Participants completed the Schutte Self-Report Emotional Intelligence Test and the Conduct and Oppositional Defiant Disorder Scales (CODDS). Regression analysis revealed that emotional intelligence significantly and negatively predicted disruptive behaviour (β = –.21, p < .01), accounting for 4.5% of the variance. Male adolescents reported significantly higher disruptive behaviour than females (t = 5.36, p < .001). These findings emphasise the role of emotional intelligence in reducing disruptive tendencies and point to the importance of gender-sensitive behavioural interventions.